THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON CEO COMPENSATION - Erick Pradinata Fondas; Putu Anom Mahadwarta; Arif Herlambang (Manajemen dan Bisnis, 2017)
This study aims to determine the factors that affect the CEO compensation. Variables used in this study include corporate social responsibility, return on assets, CEO ownership, independent board, tobin's q, firm size, and leverage. The approach used in this research is quantitative approach. The samples in this study are companies in the mining sector listed on the Indonesia Stock Exchange (BEI) in the period of 2012-2016. Based on the results of the test, the results obtained that the variables of corporate social responsibility, return on assets, CEO ownership, board independent, firm size, and leverage have a significant influence on CEO compensation Return on assets variables have a significant positive impact on CEO compensation. CEO ownership variables have a significant negative impact on CEO compensation. Variable board independent, firm size, and leverage have a significant positive impact on CEO compensation.